Hubungan Perkembangan Kognitif dan Perkembangan Motorik Halus Anak Usia 5-6 Tahun Menggunakan Media Loose Parts - Purbayani, Rini; Ali, Nabila Nurhaliza (Sekolah Tinggi Ilmu Agama Islam Putra Galuh Ciamis, 2025)
This study aims to investigate the relationship between cognitive development and fine motor development in children aged 5–6 years, utilizing loose parts media. The study used a correlational quantitative approach with 10 children as subjects. Data were collected using a validated Likert scale questionnaire and analyzed using Spearman's correlation test with the help of SPSS version 25. The results showed that most of the children's cognitive development fell into the